Assessment of Semi-chronic Toxicity and Lipid-lowering Effect of Jasminum subtriplinerve Blume Oleaceae Extract - Hong Minh, Phan; Phuong Thanh, Mai; Thi Thu Trang, Tran; My Dung, Ho (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Abstract: Jasminum subtriplinerve Blume Oleaceae is a herbal medicine widely used for weight loss and milk gland stimulation. Extract product has been generally used but has not much scientific evidence about its safety and effects. This study aimed to evaluate the semi-chronic toxicity and lipid-lowering effects of Jasminum s ubtriplinerve Blume leaf extract. The study was performed on Wistar rats and Swiss mice. For semi-chronic toxicity, extracts at doses of 18 mg/kg/day and 54 mg/kg/day showed their safety after 90 days of continuous oral administration in Wistar rats. There was no effect on body weight, hematopoietic parameters, hepatocellular destruction, or liver and kidney function in experimental rats. For the lipid-lowering effect, the extracts at 36 mg/kg/day and 108 mg/kg/day showed a marked decrease in the blood lipid indexes (total cholesterol, triglycerides, non-HDL-C) after 7 days of dosing in Swiss mice on an endogenous dyslipidemic model induced by Poloxamer-407. Keywords: Jasminum subtriplinerve Blume Oleaceae, lipid-lowering, dyslipidemia, semi-chronic toxicity.